FACTORS INFLUENCING CONTINUANCE USAGE INTENTION OF AIRLINE WEB SITES THROUGH A WEBSITE QUALITY EVALUA T!ON APPROACH - KHAN, HUMERA (2015)
The advantages of using airline websites are well documented; even then, the continuance usage intention to use airline websites is quite low compared to other information system. Evidence exists that customers long term intention to use is very important for successful adoption of information systems. The quality of website, not only depend on technological factors, but also on behavioral characteristics of customers who use it. Few studies integrate website quality evaluation with consumer behavior studies. The lack of trust and dissatisfaction of customer leads to low level continuance usage intention to use information system. However, very limited studies exist which investigate customer continuance usage intention to use airline websites.